2020
DOI: 10.3892/mmr.2020.11766
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑inflammatory effect of salusin‑β knockdown on LPS‑activated alveolar macrophages via NF‑κB inhibition and HO‑1 activation

Abstract: Inflammation of alveolar macrophages is the primary pathological factor leading to acute lung injury (ALI), and NF-κB activation and HO-1 inhibition are widely involved in inflammation. Salusin-β has been reported to contribute to the progression of the inflammatory response, but whether salusin-β could regulate inflammation in lipopolysaccharide (LPS)-induced ALI remains unknown. The present study aimed to investigate the role of salusin-β in LPS-induced ALI and to uncover the potential underlying mechanisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For example, Zhao et al revealed that NF- κ B might raise levels of miR-99b and contribute to ALI in LPS-induced mice [ 48 ]. Also, Chen et al reported that LPS enhanced phosphorylated (p)-I κ B and p-p65 levels in NR8383 cells and lung tissues [ 49 ]. Hirao et al clarified that recombinant human soluble thrombomodulin significantly decreased NF- κ B p65 expressions in lung tissue of CPB rats [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhao et al revealed that NF- κ B might raise levels of miR-99b and contribute to ALI in LPS-induced mice [ 48 ]. Also, Chen et al reported that LPS enhanced phosphorylated (p)-I κ B and p-p65 levels in NR8383 cells and lung tissues [ 49 ]. Hirao et al clarified that recombinant human soluble thrombomodulin significantly decreased NF- κ B p65 expressions in lung tissue of CPB rats [ 50 ].…”
Section: Discussionmentioning
confidence: 99%